2019
DOI: 10.1016/j.jsxm.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Early-life Chronic Stressors, Rumination, and the Onset of Vulvodynia

Abstract: Introduction Vulvodynia is a debilitating, chronic vulvar pain condition. Community-based case-control studies have consistently shown associations between early-life chronic stressors and vulvodynia onset. Aim We examined rumination as a specific stress response involved in the psychobiological mechanism of vulvodynia. Methods A psychosocial survey with ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…Similarly, Khandker et al 4 found that compared with controls, 215 women in Boston who had experienced CSA had, depending on the severity of abuse, a 1.4–9.7 AOR of experiencing vulvodynia. This was followed by a 2019 study that found rumination (repetitive, intrusive thoughts of one's negative experiences) to be another potential mediator 7 . Thus, our data showing that women with a history of CSA are twice as likely to screen positive for vulvodynia in comparison to controls (OR = 1.90, 95% CI = 1.45–2.49) further supports the relationship between CSA and vulvodynia.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Similarly, Khandker et al 4 found that compared with controls, 215 women in Boston who had experienced CSA had, depending on the severity of abuse, a 1.4–9.7 AOR of experiencing vulvodynia. This was followed by a 2019 study that found rumination (repetitive, intrusive thoughts of one's negative experiences) to be another potential mediator 7 . Thus, our data showing that women with a history of CSA are twice as likely to screen positive for vulvodynia in comparison to controls (OR = 1.90, 95% CI = 1.45–2.49) further supports the relationship between CSA and vulvodynia.…”
Section: Discussionsupporting
confidence: 71%
“…This was followed by a 2019 study that found rumination (repetitive, intrusive thoughts of one's negative experiences) to be another potential mediator. 7 Thus, our data showing that women with a history of CSA are twice as likely to screen positive for vulvodynia in comparison to controls (OR = 1.90, 95% CI = 1.45-2.49) further supports the relationship between CSA and vulvodynia. It is interesting to note that although sexual abuse is unfortunately very common, certainly not every survivor develops vulvodynia, nor does every survivor become obese.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our collective understanding of risk factors, etiologies, and effective interventions for vulvodynia continues to evolve. Histories of seasonal and contact allergies [3], recurrent urinogenital infections [31], and chronic psychological stress [32,33] have all been positively associated with individual- and population-level vulvodynia risk. In our previously published work, we have demonstrated the biological plausibility of contact allergy reactions in labiar skin [7,8] and vaginal canal [9] tissues, driving subsequent persistent painful sensitivity to touch in the ano-genital ridge of ND4 female mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall evidence is still relatively limited, and some studies question the role of inflammation in driving LPV (Chalmers et al, 2016). Stressinduced life factors (Harlow and Gunther Stewart, 2005;Khandker et al, 2011;Khandker et al, 2014;Khandker et al, 2019) can also trigger an immunological tissue response. The pathogenesis of primary LPV and secondary LPV may also differ so that the microbial cause is more likely related to secondary LPV.…”
Section: Pathogenesismentioning
confidence: 99%